A comercialização dos artefatos de miriti: as influências culturais e o impacto sócioeconômico e ambiental do município de Abaetetuba - PEREIRA, Francineide Santos (2024)
n this work of completion regarding the international marketing of toys miriti , aiming to identify how occurs and the influences that triggered the lives of artisans , as well as environmental aspects of this activity in the future . It is fact that many changes have occurred , some partnerships have been made , especially with SEBRAE , which is developing a working commercial orientation and marketing with the artisans , as well as workshops to improve the designer of toys miriti , using the best materials for finishing . Bibliographical research and structured interviews and structures associations and some artisans workshops were held . Currently toys miriti are considered in the world , a major regional symbols of the State of Pará , and each year , in each exposure within or outside the State and Brazil gain more spaces as a peculiar craft the municipality of Abaetetuba.